2016
DOI: 10.1111/jne.12402
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogens and Progestagens: Synthesis and Action in the Brain

Abstract: When steroids, such as pregnenolone, progesterone and oestrogen, are synthesised de novo in neural tissues, they are more specifically referred to as neurosteroids. These neurosteroids bind specific receptors to promote essential brain functions. Pregnenolone supports cognition and protects mouse hippocampal cells against glutamate and amyloid peptide-induced cell death. Progesterone promotes myelination, spinogenesis, synaptogenesis, neuronal survival and dendritic growth. Allopregnanolone increases hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 159 publications
(252 reference statements)
2
75
0
1
Order By: Relevance
“…However, basic research is also needed to better understand how other factors may influence the bioavailability of peripheral hormone levels, such as individual differences in aromatase activity (which converts testosterone to estradiol)(Lephart, Simpson et al. 1992), de novo steroid synthesis in brain tissues (Pelletier 2010, Rossetti, Cambiasso et al 2016), and variation in the composition and neural location of sex steroid receptors as a function of pubertal development (Kashon and Sisk 1994). …”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…However, basic research is also needed to better understand how other factors may influence the bioavailability of peripheral hormone levels, such as individual differences in aromatase activity (which converts testosterone to estradiol)(Lephart, Simpson et al. 1992), de novo steroid synthesis in brain tissues (Pelletier 2010, Rossetti, Cambiasso et al 2016), and variation in the composition and neural location of sex steroid receptors as a function of pubertal development (Kashon and Sisk 1994). …”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…This hormone plays essential roles in regulation of female characteristics and is also involved in development and homeostasis of several tissues. In addition to the reproductive system, estrogen also affects brain, kidney, heart, and so on. Several lines of evidence have reported that estrogen can regulate protein expression, oxidative stress, and ATP synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens are involved in maintaining brain function (Galea, Frick, Hampson, Sohrabji, & Choleris, ; Rossetti, Cambiasso, Holschbach, & Cabrera, ). These hormones interact with different receptors, including alpha and beta estrogen, which are present in the brain (Almey, Milner, & Brake, ; Mikosha, Kovzun, & Tronko, ).…”
Section: Discussionmentioning
confidence: 99%